Reflective Activity as a Promoter of Awareness Processes in College Students: A Study - Mollo, Monica; Iannaccone, Antonio; Savarese, Giulia; Pecoraro, Nadia; Fasano, Oreste; D’Elia, Daniela; Manzi, Federico; Moccia, Giuseppina (Frontiers in Education, 2022)
As the literature clearly shows, supporting the development of reflective awareness skills is undoubtedly an important element in learning processes. In psychology, multiple theoretical approaches and research work have delved into the study of what is termed implicit knowledge. In particular, the relationship between human activity (in terms of actions, thoughts, beliefs, motivation, and reasoning) and different levels of awareness is a relevant subject of analysis that we consider as the core of this paper. In order to deepen our understanding of the concepts of awareness and reflexive activity, we refer to Pierre Vermersch's psycho-phenomenological approach and Piaget's theory of cognitive awareness. In this paper, we aim to show the use of the reflective approach centered on the elicitation of specific lived experiences. The objective is to promote in students a process of awareness of their activity and their role within the university context. Two students case studies from the University of Salerno took part in the research. The method used was based on narrative interviews that makes use of some techniques and principles of elicitation interviews, a conversational approach that supports the participant in focusing and describing a specific experience. The interviewer guides subjects, without induction, through the transition from the implicit of lived experience (particularly action) to the explicit of reflected awareness of that action. The data collected show how reflective activity by means of guided evocations of lived experiences helped participants become aware of how some distortions and irrational thoughts (related to the self and context) negatively affected them during the activities. The reflective work fostered by the elicitation of experiences often allows for enhanced self-awareness; the subject takes ownership of the action, analyzes it, and understands the difficulties.